Determination of bacterial toxin toxoflavin and fervenulin in food and identification of their degradation products. (15th January 2023) - Wang, Hui; Hu, Lili; Chang, Xiaotu; Hu, Yuge; Zhang, Yan; Zhou, Peng; Cui, Xiaojiao
Highlights: A method for the determination of toxoflavin and fervenulin in food was developed. Different pretreatments were performed for 6 types of food. The stability of toxoflavin and fervenulin was investigated for the first time. Degradation products of toxoflavin and fervenulin were identified by UHPLC-Q-TOF. Abstract: A method using ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) was developed for the determination of toxoflavin and fervenulin in 6 types of food. The limits of detection (LODs, S/N ≥ 3) of toxoflavin and fervenulin reached 12 µg/kg and 24 µg/kg, respectively. The recoveries ranged from 70.1 % to 108.7 %. Intra-day RSDs (n = 5) and inter-day RSDs (n = 3) ranged from 0.9 % to 9.5 %. The method was successfully applied to analyse 36 samples, and one Tremella fuciformis Berk. sample was found with 7.5 mg/kg toxoflavin and 3.2 mg/kg fervenulin. Toxoflavin and fervenulin were acidic compounds and easily degraded in 0.1 % ammonia solution (v/v), degradation products were identified by ultra-high performance liquid chromatography-tandem quadrupole time-of-flight mass spectrometry (UHPLC-Q-TOF/MS).